Cost-Utility Analysis of Camrelizumab Plus Chemotherapy Versus Chemotherapy Alone as a First-Line Treatment for Advanced Nonsquamous Non-Small Cell Lung Cancer in China - Chen, Ting; Xie, Ruixiang; Zhao, Qiuling; Cai, Hongfu; Yang, Lin (Frontiers in Oncology, 2022)
Purpose: To evaluate the cost utility of camrelizumab plus standard chemotherapy versus standard chemotherapy alone as a first-line treatment for advanced nonsquamous non-small cell lung cancer (NSCLC) from the perspective of the Chinese health care system and to provide a reference for health decision-making. Methods: A Markov model consisting of three health states was designed to evaluate the cost utility of these two treatment regimens for NSCLC patients with the incremental cost-effectiveness ratio (ICER) as the primary output indicator. Clinical data were derived from a published phase III clinical trial (CameL; ClinicalTrials.gov; NCT03134872). One way sensitivity analysis and probabilistic sensitivity analysis were performed to assess the model uncertainty. Results: Base case analysis showed that the ICER of camrelizumab plus chemotherapy compared with chemotherapy alone was $43,275.43 per QALY. It was higher than the willingness-to-pay (WTP) threshold of $31,510.57 per QALY in China, which has a standard of three times the GDP per capita recommended by the WHO. One way sensitivity analysis showed that the utility value of PFS had the greatest influence on the results, and the other sensitive parameters were the cost of subsequent second-line therapy in the two group, the pemetrexed price, the cost of adverse event management and the utility value of PD. The probability sensitivity analysis showed that the probabilities of the cost-effectiveness of camrelizumab plus standard chemotherapy were 27.1%, 66.7% and 88.0% when the WTP values were $40,000, $50,000 and $60,000 per QALY, respectively. Conclusions: Taking three times the GDP per capita in China as the WTP threshold, the camrelizumab plus standard chemotherapy regimen does not have a cost-effectiveness advantage compared with the standard chemotherapy regimen alone as a first-line treatment for advanced NSCLC.